(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The study considers an attempt to analyze somatic paroemias with a numerical component in the Kyrgyz language and determine their meanings and features. Somatic paremes of numerical value in the Kyrgyz language are a certain system of lexical units that have a fixed number of meanings in the human body. These paremias symbolically represent a person’s inner world, emotions, and actions through the human body. Somatic paremes of numerical value are used in language in metaphorical ways to deepen various concepts and often describe social and private life. They serve the development of the language, do not depend on the national language, but on the individual characteristics of the language, and may differ both quantitatively and qualitatively. The semantic and quantitative meaning of somatic paroemias with a numerical component as a whole often implies the unity of people and a quantitative indicator of spiritual values forgotten in society and the development of society.